2018
DOI: 10.1140/epjds/s13688-018-0132-1
|View full text |Cite
|
Sign up to set email alerts
|

A scalable method to quantify the relationship between urban form and socio-economic indexes

Abstract: The world is undergoing a process of fast and unprecedented urbanisation. It is reported that by 2050 66% of the entire world population will live in cities. Although this phenomenon is generally considered beneficial, it is also causing housing crises and more inequality worldwide. In the past, the relationship between design features of cities and socio-economic levels of their residents has been investigated using both qualitative and quantitative methods. However, both sets of works had significant limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 22 publications
0
25
0
4
Order By: Relevance
“…We illustrate control on sediment hazard by built fabric in the context of coastal hurricanes, but the premise of our analysis extends to flow-driven hazards in tsunami, fluvial, debris-flow, and volcanic contexts. Research is beginning to demonstrate links between fabrics and socioeconomic metrics as a means of informing spatial planning and urban design (Venerandi et al, 2018). Two key goals of the Sendai Framework for Disaster Risk Reduction (2015-2030) are to "reduce direct economic loss in relation to [gross domestic product]" and to "reduce disaster damage to critical infrastructure and disruption of basic services" (UN, 2015).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…We illustrate control on sediment hazard by built fabric in the context of coastal hurricanes, but the premise of our analysis extends to flow-driven hazards in tsunami, fluvial, debris-flow, and volcanic contexts. Research is beginning to demonstrate links between fabrics and socioeconomic metrics as a means of informing spatial planning and urban design (Venerandi et al, 2018). Two key goals of the Sendai Framework for Disaster Risk Reduction (2015-2030) are to "reduce direct economic loss in relation to [gross domestic product]" and to "reduce disaster damage to critical infrastructure and disruption of basic services" (UN, 2015).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…In recent years, quantitative studies have emerged, in part as a result of technological development, which have advanced the understanding of urban environments through digital processing and statistical analysis of large-scale fine-grained data sets. Such studies have found links between urban form and a wide range of issues, such as health, energy consumption, and liveability of neighbourhoods [5][6][7]. However, such analyses have only been applied to the study of informal settlements to a limited degree, particularly in the context of Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…However, the urban environment is a much more complex entity, characterised by multiple factors that act together rather than in isolation [7,8]. More recently, a methodology to study socioeconomic indexes that accounted for multiple urban features and utilised multivariate spatial regression rather than correlation has been proposed [9]. It was tested on six UK cities and showed that more population density, unbuilt land, and dead-end roads, as well as a more regular street layout were associated with more socioeconomically deprived neighbourhoods.…”
Section: Introductionmentioning
confidence: 99%